Development of Biology Module Based on Local Potential of Coffee Plants (Coffea sp.) on Inheritance Pattern Materials for Third Class of Senior High School - Rosalvin, Suqya Rahmah; Anas, Nirwana; Khairuna, Khairuna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
The research aims to determine: (1) the feasibility level of the module based on the local potential of Biology; (2) the level of practicality of the biology module; and (3) the level of effectiveness of the use of biological modules based on local potential of coffee plants (Coffea sp.) on the material of inheritance patterns. Development research includes the following stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The test subjects consisted of media experts, material experts, linguists, and 1 MGMP teacher with 40 students at MAS Miftahussalam, 10 students as small group trials and 30 students as large group trials. Data were obtained using a questionnaire and a test sheet. The data were analyzed using quantitative descriptive analysis techniques. The results showed that: (1) the feasibility of the media was in the very feasible category (94.54%); (2) The biology module material is in the very feasible category (87.63%); (3) The language is in the very feasible category (91.66%); (4) Practicality obtained from MGMP teachers is in the very practical category (94.75%); (5) The trial of 40 students was in the practical category (76.48%); and (6) the effectiveness obtained by n-gain of 0.71 with the effective category. Based on the results of the study, it can be concluded that the biology module based on the local potential of the coffee plant (Coffea sp.) on the material of inheritance patterns is very feasible, practical, and effective in improving the learning outcomes of class XII students